Increased Ion Conductivity in Composite Solid Electrolytes With Porous Co3O4 Cuboids - Zhou, Qiongyu; Liu, Songli; Zhang, Shiju; Che, Yong; Gan, Li-Hua (Frontiers in Materials, 2021)
Compared with the fagile ceramic solid electrolyte, Li-ion conducting polymer electrolytes are flexible and have better contact with electrodes. However, the ionic conductivity of the polymer electrolytes is usually limited because of the slow segment motion of the polymer. In this work, we introduce porous Co3O4 cuboids to Poly (Ethylene Oxide)-based electrolyte (PEO) to investigate the influence of these cuboids on the ionic conductivity of the composite electrolyte and the performance of the all-solid-state batteries. The experiment results showed the porous cuboid Co3O4 fillers not only break the order motion of segments of the polymer to increase the amorphous phase amount, but also build Li+ continuous migration pathway along the Co3O4 surface by the Lewis acid-base interaction. The Li+ conductivity of the composite polymer electrolyte reaches 1.6 × 10–4 S cm–1 at 30 oC. The good compatibility of the composite polymer electrolyte to Li metal anode and LiFePO4 cathode ensures good rate performance and long cycle life when applying in an all-solid-state LiFePO4 battery. This strategy points out the direction for developing the high-conducting composite polymer electrolytes for all-solid-state batteries.